Periodontitis and low cognitive performance: A population‐based study. (27th January 2023) - Marruganti, Crystal; Baima, Giacomo; Aimetti, Mario; Grandini, Simone; Sanz, Mariano; Romandini, Mario
Abstract: Aim: To study the epidemiological association between periodontitis and low cognitive performance among older adults, within a representative sample of the U.S. population. Materials and Methods: Data from 2086 older adults (≥60 years old), representative of 77.1 million people, were retrieved from the NHANES 2011‐2014 database. Periodontitis cases were identified and classified according to the AAP/CDC criteria (mild, moderate, and severe). Cognitive function was assessed through the Consortium to Establish a Registry for Alzheimer's disease (CERAD), the animal fluency test (AFT), the digit symbol substitution test (DSST), and the global cognition score. The lowest non‐survey weighted quartile for each cognitive test was defined as low cognitive performance. Simple and multiple regression analyses were performed. Results: Moderate and severe periodontitis were significantly associated with a low DSST performance (OR = 1.66 and OR = 2.97, respectively). Each millimetre increase in mean CAL was associated with a lower AFT (OR = 1.44), DSST (OR = 1.86), and global cognition (OR = 1.50) performance. Conclusions: The findings of the present study suggest the existence of an independent association between periodontitis and low cognitive performance among older adults (≥60 years old).